Current Status of Pyroprocessing Development at KAERI. (11th March 2013) - Lee, Hansoo; Park, Geun-IL; Lee, Jae-Won; Kang, Kweon-Ho; Hur, Jin-Mok; Kim, Jeong-Guk; Paek, Seungwoo; Kim, In-Tae; Cho, IL-Je
Abstract : Pyroprocessing technology has been actively developed at Korea Atomic Energy Research Institute (KAERI) to meet the necessity of addressing spent fuel management issue. This technology has advantages over aqueous process such as less proliferation risk, treatment of spent fuel with relatively high heat and radioactivity, and compact equipments. This paper describes the pyroprocessing technology development at KAERI from head-end process to waste treatment. The unit process with various scales has been tested to produce the design data associated with scale-up. Pyroprocess integrated inactive demonstration facility (PRIDE) was constructed at KAERI and it began test operation in 2012. The purpose of PRIDE is to test the process regarding unit process performance, remote operation of equipments, integration of unit processes, scale-up of process, process monitoring, argon environment system operation, and safeguards-related activities. The test of PRIDE will be promising for further pyroprocessing technology development.